Model Pendekatan Manajemen Resiko Keamanan Dalam e-Commerce - Wismantoro Yohan (Semantik, 2011)
ABSTRACT: E-commaerce security is a complex issue; it is concerned wiht a number of security risks that can appear at either a technical level or organisational level. This paper uses a systemic framework, the viable system model (VSM) to determine the high level security risks and then uses baseline security methods todetermine the lower level security risks.Keyword: Electronic commerce, Risk analysis, Information system